2013
DOI: 10.1111/1754-9485.12019
|View full text |Cite
|
Sign up to set email alerts
|

New scanning technique using Adaptive Statistical Iterative Reconstruction (ASIR) significantly reduced the radiation dose of cardiac CT

Abstract: Application of ASIR reduces the radiation dose of CCTA without affecting the image quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 6 publications
1
28
1
Order By: Relevance
“…The 14 studies recruited a total sample size of 3428 patients . The ratio of male to female was 1664 to 1706 patients, one study did not provide the ratio between gender (Table ) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 14 studies recruited a total sample size of 3428 patients . The ratio of male to female was 1664 to 1706 patients, one study did not provide the ratio between gender (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…These include the electrocardiogram (ECG) gating method used, detector collimation size, gantry rotation time, tube voltage and tube current. A total of seven studies used prospective ECG‐gating, two studies used retrospective, and four studies used both types . One study did not provide the type of ECG‐gating used .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Retrospective analyses showed comparable results, with one study demonstrating a 24% dose reduction among patients undergoing coronary CTA with ASiR reconstruction compared to FBP despite no differences in signal intensity, signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), or diagnostic quality. 8 Gosling et al 9 demonstrated that while coronary CTA with FBP reconstruction resulted in a similar dose to invasive coronary angiography (ICA) (5.4 mSv vs 6.3 mSv), there was a 54% dose reduction using ASiR reconstruction (2.5 mSv) (Fig. 1).…”
Section: Adaptive Statistical Iterative Reconstructionmentioning
confidence: 99%
“…1,2 IR methods have been successfully applied in cardiovascular, 3,4 thoracic, [5][6][7][8] abdominal, 9,10 and head CT applications. [11][12][13][14] This study used a commercially available advanced IR technique, sinogram-affirmed iterative reconstruction.…”
mentioning
confidence: 99%